A diagnostic solution for haemostasis laboratories for patients taking direct oral anticoagulants using DOAC‐Remove. (10th July 2019) - Cox‐Morton, Sally; MacDonald, Stephen; Thomas, Will
Summary: This study describes the use of a simple charcoal product (DOAC‐Remove TM ) to allow haemostasis assays on patients taking direct oral anticoagulants (DOAC). In the proposed algorithm, patients taking DOAC are screened using the dilute thrombin time (dTT) and anti‐Xa assay. If either are positive then DOAC‐Remove is utilised. In a validation, DOAC‐Remove did not interfere with coagulation testing in normal plasma or in patients on DOAC with a known lupus anticoagulant (LA). Of 1566 routine patient samples tested, 125 (8%) had evidence of anti‐Xa activity (>0·1 iu/ml) or prolonged dTT suggestive of either a direct/indirect Xa inhibitor or direct thrombin inhibitor. All of these 125 patients had a prolonged dilute Russell viper venom time (dRVVT) screening test and 106 had a LA detected by dRVVT after phospholipid correction. After DOAC‐Remove, 91 patients (73%) had a negative dRVVT screen. After further investigation only 9 (7%) had a positive LA. DOAC‐Remove prevented 5% of patients having a LA inappropriately detected. DOAC did not significantly affect the LA activated partial thromboplastin time (aPTT) ratio, protein S antigen or protein C activity. DOAC cause low intrinsic factor assays, high prothrombin time/aPTT and high activated protein C sensitivity ratio, which DOAC‐Remove reversed ( P  < 0·05). Despite recommendations, haemostasis testing for patients on DOAC continues; this algorithm aids diagnostic accuracy. Further validation and research are warranted.